Effect of patient–ventilator asynchrony on lung and diaphragmatic injury in experimental acute respiratory distress syndrome in a porcine model. (January 2023) - Wittenstein, Jakob; Huhle, Robert; Leiderman, Mark; Möbius, Marius; Braune, Anja; Tauer, Sebastian; Herzog, Paul; Barana, Giulio; de Ferrari, Alessandra; Corona, Andrea; Bluth, Thomas; Kiss, Thomas; et al.
Abstract: Background: Patient–ventilator asynchrony during mechanical ventilation may exacerbate lung and diaphragm injury in spontaneously breathing subjects. We investigated whether subject–ventilator asynchrony increases lung or diaphragmatic injury in a porcine model of acute respiratory distress syndrome (ARDS). Methods: ARDS was induced in adult female pigs by lung lavage and injurious ventilation before mechanical ventilation by pressure assist–control for 12 h. Mechanically ventilated pigs were randomised to breathe spontaneously with or without induced subject–ventilator asynchrony or neuromuscular block ( n =7 per group). Subject–ventilator asynchrony was produced by ineffective, auto-, or double-triggering of spontaneous breaths. The primary outcome was mean alveolar septal thickness (where thickening of the alveolar wall indicates worse lung injury). Secondary outcomes included distribution of ventilation (electrical impedance tomography), lung morphometric analysis, inflammatory biomarkers (gene expression), lung wet-to-dry weight ratio, and diaphragmatic muscle fibre thickness. Results: Subject-ventilator asynchrony (median [interquartile range] 28.8% [10.4] asynchronous breaths of total breaths; n=7) did not increase mean alveolar septal thickness compared with synchronous spontaneous breathing (asynchronous breaths 1.0% [1.6] of total breaths; n=7). There was no difference in mean alveolar septal thickness throughout upper and lower lung lobes between pigs randomised to subject–ventilator asynchrony vs synchronous spontaneous breathing (87.3–92.2 μm after subject–ventilator asynchrony, compared with 84.1–95.0 μm in synchronised spontaneous breathing;). There were also no differences between groups in wet-to-dry weight ratio, diaphragmatic muscle fibre thickness, atelectasis, lung aeration, or mRNA expression levels for inflammatory cytokines pivotal in ARDS pathogenesis. Conclusions: Subject–ventilator asynchrony during spontaneous breathing did not exacerbate lung injury and dysfunction in experimental porcine ARDS.